Cracking the code: Unveiling dividend policy factors in Palestine’s stock exchange (PEX) - Alslaibi, Naji Anton (Edelweiss Applied Science and Technology, 2024)
This study aims to enrich the literature on dividend policy by better understanding the factors and determinants affecting dividends. This study used 11 independent variables from secondary data, balanced panel techniques, and fixed and random effect regressions for 29 listed companies over seven years. The results indicate a favorable association between (earnings per Share, Cash flow, Firm Size, and Lagged dividends) and dividend payout ratios. None of the other predictors were significant in the regression analysis. This is the first study that comprehensively covers dividend policy using 11 variables identified by researchers. Since this area of research is still considered a puzzle, this study presented an improved model with a 75% model fit. Policymakers should revise current dividend policy disclosure to serve investors' needs and goals. Future research includes understanding cultural norms, expanding the sample size, and possibly subdividing observations into sectoral categories.